Final results of the SENECA (SEcond line NintEdanib in non-small cell lung CAncer) trial. (August 2019) - Capelletto, Enrica; Migliorino, Maria Rita; Morabito, Alessandro; Chiari, Rita; Grossi, Francesco; Tiseo, Marcello; Costanzo, Francesco Di; Delmonte, Angelo; Romano, Gianpiero; Galetta, Domenico; Scotti, Vieri; Gregorc, Vanesa; et al.
Highlights: SENECA didn't show differences between weekly and q3wks docetaxel plus nintedanib. No differences were noticed between relapse timing cohorts from end of chemotherapy. Higher toxicities for q3wks docetaxel arm have been found. Quality-of-life was stable during study in both treatment groups and cohorts. Abstract: Objectives: Despite the scant docetaxel's tolerability, second-line association with nintedanib still represents a standard-of-care for non-squamous non-small cell lung cancer (nsNSCLC), giving to rapidly-progressing patients the greatest survival advantage. The SENECA trial is a phase IIb, open-label, study evaluating whether nintedanib/docetaxel can be equally effective and safe regardless docetaxel schedule. Materials and Methods: Recurrent nsNSCLC patients were stratified into cohort 1 and 2, according to relapse-time (within or over 3 months) from end of first-line chemotherapy. They were treated with docetaxel (T1: 33 mg/mq on days 1 and 8 in a 21-days cycle; T2: 75 mg/mq q3wks) plus nintedanib, allowing maintenance in case of disease-control. Primary endpoint was progression-free survival (PFS) by investigator's assessment; secondary endpoints: overall survival (OS), safety and quality-of-life. Results: Between January 2016-April 2018, 212 patients were evaluated: 30 resulted screening-failures, 12 were excluded for lack of compliance. According to investigator's choice, 85 patients received T1 docetaxel and 85 T2; 138 (81.2%) were stratified in C1, 32 (18.8%) in C2, with a median relapse-time of 0.54 and 9.29 months, respectively. Baseline characteristics were balanced between groups. After 35.5 months follow-up, no survival differences appear between cohorts and treatments; toxicity seems to be slightly higher in T2, especially for chemotherapy-related events. Perception of quality-of-life remains stable and docetaxel schedule doesn't modify patients' load. Conclusion: The SENECA trial confirms efficacy of second-line nintedanib/docetaxel for nsNSCLC, regardless time of recurrence and docetaxel schedule; higher toxicities for q3wks docetaxel, without alterations in quality-of-life, have been described, underling the possibility, adopting the weekly schedule, to maintain efficacy with better tolerability.